DEVELOPING A COOPETITION MODEL IN THE IRAN BANKING INDUSTRY - Narges HasanBeygi, Asadollah Kordnaeij, Morteza Soltani, Hamidreza Irani (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This paper aims to develop a coopetition model in the Iran banking industry. The type of research can be quantitative, qualitative or a combination of both, which in this study combined methodology (qualitative-quantitative) was used. The strategy of this research is grounded theory and case study. The research population in the qualitative phase was managers and senior experts in the banking industry, which was conducted by snowball method, saturation until the thirty-third interview, and thus 33 interviews were conducted in this study. The statistical population of the quantitative part of this research includes all managers and senior experts and heads of departments, units and branches in the banking industry. Finally, 368 questionnaires were collected at random. For validation verification four criteria of validity including transferability, reliability and verification were used. Instrument reliability in the quantitative part of this study, the reliability coefficients of the questionnaire were calculated and confirmed by Cronbach's alpha method of 0.76. Data analysis in the qualitative part, the grounded theory method was used and in the quantitative part, the statistical methods of structural equations were used. According to the research findings, in the dimension of challenges of the banking industry, international challenges, technology, human resources, changing environment and structural and managerial, in the dimension of willingness to cooperate with competitors, value creation, the possibility of allocating value, seizing that opportunity demand, foresight of managers and decision makers, the appropriateness and compatibility of goals and strategies between two competitors, complementarity of resources and capabilities of the two competitors, the possibility of exchanging technologies, the ability to manage conflict and the possibility of exchanging knowledge and information. In the dimension of the banking industry challenges, the economic environment, socio-cultural environment, political-legal environment and technology environment, in the intervening conditions of human resources, organizational structure, technology, organizational culture, financial resources, senior management and macro policies and finally in The the coopetition strategies of the of joint venture, currency, facilities, consulting services and the consequences were identified using organizational, social and economic factors. Finally, it can be concluded that by using the steps and types of models in the field of coopetition, relying on local knowledge and research on existing issues, a competitive advantage can be created for the banking industry.